Conceptualización del miedo en el registro coloquial del español - Gołąb, Agata (Neophilologica, 2012)
The present paper deals with the conceptualization of fear in the Spanish language and its main aim is to prove that a considerable part of our conceptual system is metaphorical. When expressing fear we frequently refer to the conceptual metaphor the source domain of which lies in the parts of the human body, in the paper illustrated by a selection of colloquial phrases denoting fear in Spanish. In many cases the associations between a particular body part (the heart or male sex organs) and the emotion in question reveals a pejorative character of fear. Metaphors are an effective tool in expressing the concepts generally regarded as abstract.